PAKAIAN SEBAGAI GEJALA MODERNITAS (Kajian Surat Al-Ahzab Ayat 59 dan Surat Al-Nur Ayat 31) - Hartini, Dwi (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
Clothing is often referred to as a form of identity or a measure of one's religiosity. So by looking at the development of modernization, this paper aims to describe the intrinsic meaning of clothing. The gap in shari'ah understanding and social reality that causes the birth of various views about clothing. Using the theory of social construction, the author tries to trace the propositions of the Al-Qur'an text which are often used to explain the command to dress according to the shari'ah. The results of this study are, clothing according to its development has a hidden modernization ideology. First, as a fashion trend that is often used in certain moments such as marriage, recitation, social gathering, and others. Second, as consumptive practices. A variety of clothing models are offered from the start of Muslim fashion shows to special Muslim clothing boutiques for sale at the mall. Third, as a personal symbol that can show a particular social class.